The effective elements of the in-store display to stimulate purchase of apparels at Metrojaya Mid Valley / Siti Hajar Mohd Kasim - Mohd Kasim, Siti Hajar (Faculty of Business and Management, 2006)
As we know maintaining a loyal customer is easier than gaining a new customer so most retailers are now starting to realize that the in-store displays are important in attracting customers. When a retailer presents their merchandise by putting it on a display, their goal is to turn store traffic into shoppers and shoppers into buyers. The success of the retailer depends on the kind and quality of display that they used. The purpose of this study is to analyze the effective elements and relationship between the in-store display and purchase of apparels at Metrojaya Mid Valley. Besides that the researcher would like to know the purchase probability that customers would make based from the in-store display. The data come from a study of 100 respondents who walk into the departmental store and view the display. The variables are merchandise, shelf or display area, props, lighting, copy cards and purchase probability. A non probability sampling technique and judgment sampling has been chosen to use. Data is analyzed using SPSS software by frequency and spearman rank order correlations. From the findings, majority of respondents perceive that the elements of the in-store display effective and highly effective. A good possibility of apparels purchasing would be made by respondents based from the in-store display. Finally, there is a moderate strength of significant relationship between the in-store display and purchase of apparels.